Improving Scientific Creative-Thinking Ability of Primary School Students through CRH Learning Model - Fasha, Linda Hania; Ruqoyyah, Siti (Mimbar Sekolah Dasar, 2020)
This research is motivated by the low creative thinking ability of the fourth-grade primary school students in Cimahi City. The purpose of this research is to examine the achievement and improvement of creative thinking abilities of primary school students between those who used the Course Review Hooray (CRH) learning model assisted by monopoly game and those who used conventional learning. This research is a quasi-experimental type with a pretest-posttest control group design. The population in this study was the fourth-grade primary school students in Cimahi City, while the sample was determined using a purposive sampling technique obtained by class 4B as an experimental class with 35 students and class 4C as a control class with 35 students. The research instrument was a science creative thinking ability test. The results showed that the achievement and improvement of creative thinking abilities of primary school students with the CRH learning model assisted by monopoly game media was better than those who used ordinary learning.